Quantcast

Got Homework?

Connect with other students for help. It's a free community.

  • across
    MIT Grad Student
    Online now
  • laura*
    Helped 1,000 students
    Online now
  • Hero
    College Math Guru
    Online now

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

shubham.bagrecha Group Title

Prove that: cos(A+B)+sin(A-B)=2sin(45+A)cos(45+B)

  • one year ago
  • one year ago

  • This Question is Closed
  1. shubham.bagrecha Group Title
    Best Response
    You've already chosen the best response.
    Medals 0

    \[ \cos(A+B)+\sin(A-B)=2\sin(45+A)\cos(45+B)\]

    • one year ago
  2. Neo92 Group Title
    Best Response
    You've already chosen the best response.
    Medals 1

    first write cos(A+B) as sin[90-(A+B)] then use sinC + sinD = 2sin[(C+D)/2]cos[(C-D)/2] try and tell me what u get

    • one year ago
  3. mathslover Group Title
    Best Response
    You've already chosen the best response.
    Medals 0

    ok ... for this first of all tell me what is cos(A+B)

    • one year ago
  4. shubham.bagrecha Group Title
    Best Response
    You've already chosen the best response.
    Medals 0

    @Neo92 ok i will solve

    • one year ago
  5. mathslover Group Title
    Best Response
    You've already chosen the best response.
    Medals 0

    cos(A+B)=sin(90-A-B) sin(90-A-B) + sin(A-B) = 2sin(45+A)cos(45+B) we know that sin(x) + sin(y)=2sin([x+y]/2)cos([x-y]/2)

    • one year ago
  6. mathslover Group Title
    Best Response
    You've already chosen the best response.
    Medals 0

    so we get that sin(90-A-B) + sin(A-B)=2sin(45-B)cos(45-A) but we know that sin(45-B)=cos(90-(45-b))=cos(45+B) and cos(45-A)=sin(90-(45-A))=sin(45+A) hence we get that cos(A+B) + sin(A-B) = 2sin(45+A)cos(45+B)

    • one year ago
  7. klimenkov Group Title
    Best Response
    You've already chosen the best response.
    Medals 2

    \[\cos(A+B)+\sin(A-B)=\cos A\cos B-\sin A\sin B+\sin A \cos B-\sin B\cos A=\] \[=\cos A(\cos B-\sin B)+\sin A (\cos B-\sin B)=(\cos A+\sin A)(\cos B-\sin B)\] Now use: \(\cos A+\sin A=\sqrt2\cdot(\frac1{\sqrt2}\cos A+\frac1{\sqrt2}\sin A)=\sqrt2\sin(45^\circ +A)\) and \(\cos B-\sin B=\sqrt2\cdot(\frac1{\sqrt2}\cos B-\frac1{\sqrt2}\sin B)=\sqrt2\cos(45^\circ +B)\). Now multiply this: \[(\cos A+\sin A)(\cos B-\sin B)=\sqrt2\sin(45^\circ +A)\cdot \sqrt2\cos(45^\circ +B)=2\sin(45^\circ +A)\cdot\]\[\cdot\cos(45^\circ +B)\]

    • one year ago
    • Attachments:

See more questions >>>

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.